Analisis Pemanfaatan Turbin Savonius Pada Pembangkit Listrik Tenaga Bayu di Desa Pantai Buaya Kabupaten Langkat - Heru Irwansyah; Zulkarnain Lubis; Rahmaniar (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The Salvonius wind turbine is one of the Vertical Axis Wind Turbines (VALWT) commonly used in wind farms. This type of turbine is usually used for medium and low wind speeds. It has a simple design, consisting of a single main rotor that rotates vertically. The advantage is that it can use wind from all directions, can work at low speeds and does not require a tower that is too high. The aim of this study was to analyse the performance of the turbine in relation to the rotation and power of the land generator. The method used was to directly measure the rotation of the turbine and the generator in no-load and load conditions. The results of the study showed that the average wind speed in Oenalli village was 4.66 m/s, and this turbine was able to rotate the Salvonius turbine with an average rotation of 631 rpm. It was then able to produce an output of 7.20 MW at a general turbine speed of 1,243 rpm. In addition, the average generator efficiency was 35%, the highest daily efficiency was 39% and the lowest daily efficiency was 37%.